Efektivitas Pemanfaatan Posyandu Lanjut Usia - Masluroh Masluroh; Lili Farlikhatun (Poltekkes Kemenkes Surakarta, 2020)
Background: The elderly Posyandu is an integrated service post for the elderly that is driven by the community to be able to get health services. The coverage of elderly health services in Bekasi City in 2013 has generally reached the target. The RPJMD and SPM targets are 70%, the health service achievement of the elderly reaches 84.2%, but there are still Puskesmas that have not yet reached the target of one, Jati Bening Health Center. The purpose of this study was to determine the factors related to the use of elderly Posyandu.Methods: The place of research is in the working area of ​​the Jatibening Health Center and was carried out in 2019. This study used an analytical survey method with a cross sectional approach. The population in this study are the elderly who are registered in the Posyandu of the elderly in the working area of ​​the Jatibening Health Center totaling 100 people, a sample of 80 respondents using the Simple Random Sampling technique. Data collection by check list and questionnaire, the data is analyzed using univariate and bivariate analysis with Chi-square.Results: The results showed there was a relationship between the knowledge of the elderly (P 0.037), family support (0.0001), and the role of cadres (P 0.01) with the use of the elderly posyandu.Conclusion: From the results of the study it can be concluded that the factors of elderly knowledge, family support and the role of cadres in the use of elderly Posyandu greatly affect how the elderly Posyandu can be utilized properly, therefore researchers suggest for health workers to be able to improve health services by providing better health services and counseling the elderly about the benefits of posyandu for the elderly.